TAFSIR DAN WANITA (STUDI TERHADAP PENAFSIRAN GURU BAKHIET) - Mujahid, Ahmad; Arabi , Ibnu (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examines Guru Muhammad Bakhiet’s interpretation of women’s issues in the Qur’an, particularly related to verses that place women in a subordinate position, such as Surah an-Nisa’ verse 1 and Surah al-Baqarah verse 228. Using field research methods through participant observation and documentation of study recordings on YouTube, this study critically analyses how Guru Bakhiet conveys his interpretation in the context of digitalising local interpretation studies. The findings show that although Guru Bakhiet places women in a textually lower position than men, he also emphasises the importance of fair respect for women, especially in terms of girls’ education. His interpretation reflects a combination of classical patriarchal interpretation and progressive attitudes towards the treatment of women. In conclusion, Guru Bakhiet’s interpretation is ambivalent, combining women’s subordinate position with a call for fair treatment, reflecting the dynamics of local interpretation in the digital era. This study contributes to understanding gender interpretation in the digital realm and highlights the need for more comprehensive and contextual local interpretation studies.